The image of women in the novel women crying to the black moon by Dian Purnomo - Harijaty, Erny; Syukur, La Ode; Ismaya, Ismaya (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
This research aims to describe the image of the main female character in the novel Woman Who Cried to the Black Moon by Dian Purnomo. The method used in this research is descriptive qualitative. The results of this study are women's self-image in the form of character or the formation of women who are also responsible for their potential as individual beings; Physical image in the form of a physical image or a woman's body, which includes beauty, posture, and beauty, like the figure of a mage who has the physical characteristics of a woman who comes from Eastern Indonesia; a psychic image which states that women are psychological beings who think, feel, and aspire. Women were created by straight psychics who are carried away by feelings, also by magi who always feel sad when separated from their friends, social image of the role of women in the family and community environment. Within the family circle, women have roles as children, homemakers, and wives. Based on research conducted on the novel Woman Crying to the Black Moon by Dian Purnomo, it can be concluded that the image of women in it is self-image, physical image, psychological image, and social image.